The Political Economy of Infrastructure Development and Capital Interests: A Case Study of Infrastructure Development in Banyu Biru Village, Pasuruan Regency - Agus Prianto (International Publisher, 2025)
This research aims to analyze the political economy dynamics in infrastructure development in Banyu Biru Village, Pasuruan Regency, focusing on the interaction between capital interests and public policy. Using a qualitative descriptive approach, data was collected through in-depth interviews, field observations, and documentation studies. The research population includes local stakeholders, such as village government, business actors, and the local community, with a purposive sample selected based on their roles and influence in the development process. The research instruments consist of semi-structured interview guides and observation sheets.The results show that infrastructure development in Banyu Biru is influenced not only by community needs but also by capital interests striving to maximize profits through investments in the tourism sector. Although there has been an improvement in facilities and accessibility that supports local economic growth. There are indications that most economic gains tend to accumulate with certain parties who have large capital, while local communities only receive limited benefits. This finding indicates the need for more inclusive and participatory policies to ensure that infrastructure development truly provides fair benefits for all levels of society.